Economic theory by Taussig, Young, and Carver at Harvard - Johnson, Marianne F.; Samuels, Warren J., 1933- (Research in the history of economic thought and methodology ;, 2010)
This volume of Research in the History of Economic Thought and Methodology offers a unique insight into early American economic theory. The notes reproduced in this volume were taken by a student, Maurice Beck Hexter, in Economics 11-12, "Economic Theory," given by Frank William Taussig at Harvard during the academic year 1921-1922. Taken together they represent the height of economic theory being taught in graduate programs in the United States during this period. Accompanying the notes are additional essays on how these notes relate to broader economic thinking of this period, providing a comparison between the Harvard viewpoint and that of previously published presentations of economic theory at the University of Chicago and the University of Wisconsin.